2022
DOI: 10.3389/fmicb.2022.839079
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Antimicrobial Resistance, and Virulence Determinants of Group B Streptococcus in an Australian Setting

Abstract: Streptococcus agalactiae [group B Streptococcus (GBS)] is a major neonatal pathogen and also causes invasive disease in non-pregnant adults. One hundred GBS isolates (n = 50 invasive disease and n = 50 colonizing pregnant women) were characterized using capsular serotyping by latex agglutination, antimicrobial susceptibility testing, and whole genome sequencing (WGS). All isolates were susceptible to penicillin, 32% were resistant to clindamycin. Of these, two isolates had reduced susceptibility to ceftriaxone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Furthermore, the proportion of resistant strains with the clindamycin-erythromycinlevofloxacin pattern was 62.7%, and clindamycin-erythromycintetracycline-levofloxacin-chloramphenicol-resistant strains were identified. An Australian study found 32% co-resistance of clindamycin and erythromycin in 100 S. agalactiae strains (Jones et al, 2022). In Iran, the multiple-resistance rate of S. agalactiae was approximately 22% (Motallebirad et al, 2021), while in Brazil, one S. agalactiae strain exhibited a multidrug resistance pattern (de Figueiredo et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the proportion of resistant strains with the clindamycin-erythromycinlevofloxacin pattern was 62.7%, and clindamycin-erythromycintetracycline-levofloxacin-chloramphenicol-resistant strains were identified. An Australian study found 32% co-resistance of clindamycin and erythromycin in 100 S. agalactiae strains (Jones et al, 2022). In Iran, the multiple-resistance rate of S. agalactiae was approximately 22% (Motallebirad et al, 2021), while in Brazil, one S. agalactiae strain exhibited a multidrug resistance pattern (de Figueiredo et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%